A deep crust-mantle boundary in the asteroid 4 Vesta - Clenet, Harold; Jutzi, Martin; Barrat, Jean-Alix, J-A; Asphaug, Erik I.; Benz, Willy; Gillet, Philippe (Nature, 2014)
International audience The asteroid 4 Vesta was recently found to have two large impact craters near its south pole, exposing subsurface material. Modelling suggested that surface material in the northern hemisphere of Vesta came from a depth of about 20 kilometres, whereas the exposed southern material comes from a depth of 60 to 100 kilometres. Large amounts of olivine from the mantle were not seen, suggesting that the outer 100 kilometres or so is mainly igneous crust. Here we analyse the data on Vesta and conclude that the crust-mantle boundary (or Moho) is deeper than 80 kilometres.